FROM THE LAND IN THE FARM USE EFFICIENCY CALCULATION MATHEMATICS FOR MODELS WORKING EXIT - Bustonova Gulchekhra Berkinboуеvna (European Science Publishing, 2025)
Currently, mathematical models are being developed to improve the efficiency of land use by developing agricultural land and reducing the area of land suitable for use. This work is also devoted to the development of mathematical models for calculating the efficiency of land use.
Keywords: Mathematical models, agro-industrial complex, productivity, efficiency, quantitative factors, regression coefficient.